HUBUNGAN PAPARAN DEBU DENGAN KAPASITAS FUNGSI PARU PADA MASYARAKAT BERISIKO DI JALAN SILIWANGI – WALISONGO KOTA SEMARANG - Nabilah Nurhidayanti; Nurjazuli Nurjazuli; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Semarang is the sixth largest city in the world with high vehicle growth. High road density on the street has an impact on increasing levels of air pollution on area. One of the high road density street in Semarang is Siliwangi – Walisongo street. The result of dust measurement showed Siliwangi=533 µg/m3 and Walisongo=487 µg/m3. This study aimed to analyze the relationship of dust exposure with lung function in community at risk in Siliwangi – Walisongo sreet, Semarang City. This research was an observational analytic research using cross-sectional approach. It was conducted on 30 risky communities at Siliwangi-Walisongo Street which was feasible by purposive sampling to be respondents. Measurement of inhaled dust levels using Personal Dust Sampler (μ = 1.86 and SD = 1.192). Measurement of lung function of the community at risk using spirometer (μ% FVC = 73.87, SD% FVC = 20.88 and μ% FEV1 = 76.6, SD% FEV1 = 21,961). Data were analyzed by using Rank Spearman test with (= 0,05). There was no statistically significant correlation between inhaled dust content and lung function capacity (FVC prediction value (p = 0.078) and average FEV1 (p = 0.097) in risky communities at Siliwangi - Walisongo Street, Semarang City. The use of cross-sectional study is not capable to represent a history of dust exposure before the study. Environmental factors and characteristics of respondents can be a potential factor in strengthening lung function disorders. This study recommends the community to use mask to reduce dust exposure. Health Office is expected to give the information of the dangers of air pollution and the prevention of the dust exposure risks by using proper mask and a better lifestyle.